Nalar Fikih Penghulu di Kota Malang dalam Saksi Nikah Tuli - Mukhammad Nur Hadi (INKLUSI, 2021)
This article discusses the paradigm of penghulus (the marriage registrants at the office for religious affairs, KUA) in Malang City regarding the status of marriage witnesses. This study uses a philosophical normative approach to find several important points. It turns out that fiqh is dominantly used by the penghulu to limit the rights of witnesses to marriages with hearing disabilities. This is related to the internalization of maslahat in the fiqh paradigm of the penghulu which is manifested in the form of concerns about leaving fiqh, on the one hand, and the stability of following fiqh and the opinions of local ulama', on the other. Nevertheless, fiqh is still a representation of the “advocative paradigm” of the penghulu in terms of the rights of deaf marriage witnesses by elaborating on sociological aspects and the development of science. It is safe to say that the continuing reference to traditional fiqh among the penghulu is related to the failure of the Malang City government in promoting their vision of creating an inclusive city. Artikel ini membahas nalar fikih penghulu di Kota Malang dalam status saksi nikah. Penelitian ini menggunakan pendekatan normatif filosofis untuk menemukan beberapa poin penting. Fikih ternyata dominan digunakan penghulu untuk membatasi hak saksi nikah Tuli. Hal ini terkait dengan internalisasi maslahat dalam nalar fikih penghulu yang termanifestasi dalam bentuk kekhawatiran meninggalkan fikih, di satu sisi, dan kemantapan mengikuti fikih dan pendapat ulama’ lokal, di sisi yang lain. Meskipun demikian, fikih masih menjadi representasi “nalar advokatif” penghulu dalam hal hak saksi nikah Tuli dengan mengelaborasi aspek sosiologis dan perkembangan ilmu pengetahuan. Di sini dapat ditemukan bahwa dominasi nalar fikih lama di kalangan penghulu terkait dengan lemahnya pengaruh gagasan pemerintah Kota Malang yang ingin mewujudkan kota yang inklusif.